1973
DOI: 10.1136/bmj.1.5851.465
|View full text |Cite
|
Sign up to set email alerts
|

Review of Schizophrenics in a Rural Practice over 26 Years

Abstract: SummaryOver 26 years some 73 patients with schizophia were observed. Three types were considered, true schizophrenia, schizophrenia simplex, and whizoaffective disorders. Of those traced and alive in 1971, some 18% of the group had recovered, 46% had made a social recovery, 25% were unemployed in the community, and 11% were long-stay hospital patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1973
1973
2000
2000

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…Schizophrenic subjects with no such contact would not be registered on the LPCR. It has been reported that 97-5% of new cases of schizophrenia presenting to general practitioners in Scotland are referred to a psychiatrist (Watts et al 1964), but there is also evidence that some schizophrenic patients are managed entirely within primary care and are never seen by the psychiatric services (Watts, 1973). Some may avoid detection by the medical services altogether, but the very large field surveys necessary to detect such subjects have not been attempted in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…Schizophrenic subjects with no such contact would not be registered on the LPCR. It has been reported that 97-5% of new cases of schizophrenia presenting to general practitioners in Scotland are referred to a psychiatrist (Watts et al 1964), but there is also evidence that some schizophrenic patients are managed entirely within primary care and are never seen by the psychiatric services (Watts, 1973). Some may avoid detection by the medical services altogether, but the very large field surveys necessary to detect such subjects have not been attempted in the UK.…”
Section: Discussionmentioning
confidence: 99%
“…This is, however, not always the case. Thus, in his survey over 26 years of all schizophrenics occurring in a general practice population of eight thousand, Watts has reported that 15 (21 %) of the 72 schizophrenics whom he found were not admitted to hospital; furthermore, nearly three-quarters (11) of this group were not seen by a psychiatrist and over one-quarter (4) received no further medical attention (Watts, 1973). Admission to a psychiatric hospital is sometimes precipitated more by a crisis in the patient's immediate social network than by a decision made on medical grounds and will thus accord an unsatisfactory reflection of the clinical severity of the disorder (Wing, 1968).…”
Section: The Natural History Of Schizophrenia: a Five-year Follow-upmentioning
confidence: 99%
“…Thus, in his survey of general practice Watts (1973) reports a small number of schizophrenics who were not caught in the hospital net. Thus, in his survey of general practice Watts (1973) reports a small number of schizophrenics who were not caught in the hospital net.…”
Section: Limitationsmentioning
confidence: 99%
“…Research in the early years of community care for the mentally ill showed that between 9% and 11% of patients with acute schizophrenia had been treated entirely within the primary care setting ( Watts 1973, Freeman & Alpert 1986) and up to 25% of those discharged from mental health facilities had received aftercare solely from their GP ( Parkes et al . 1962 , Hassell & Stilwell 1997, Johnstone et al .…”
Section: Introductionmentioning
confidence: 99%